Status of substance abuse in girls trade high school students - Taşçı, Emel; Ünsal Atan, Şenay; Durmaz, Nazike; Erkuş, Hilal; Sevil, Ümran (Journal of Dependence, 2005)
Objective: The aim of this study was to determine knowledge levels and views of junior and senior high school students related to substance dependency and their status of using substance.Method: The scope of this research included all the students attending Karşıyaka Girls Trade School and Anatolia High School. The sampling of the study comprised all junior and senior high school students (102 students) who attended the school between the dates of 22 -26 March 2004 and accepted to take part in the research. The data was collected by using a survey form developed by researchers. In the analysis of the data, number and percentage dispersion, mean and standard deviations and Pearson chi-square analysis were used.Results: It was identified in the research that 67.6 % of the students were approximately 16-17 years old, 59.8 % were in the second grade, 15.7 % were in the third grade; of those who were using substance 31.2 % started using substance with a friend’s encouragement, 25.0 % with a desire to try and 43.1 % received training related to substance dependency.In the research, students were asked “What is substance dependency?” 32.8 % replied as “to use an illicit substance” and 29.7 % as “a bad habit”. It was determined that 47.1 % of the students stated that their friends, 26.5 % their parents, 14.7 % their boy/girl friends were using substance, the friends of 18.8 % and the boy/girl friends of 6.6 % were using ecstasy. It was also detected that 31.4 % of the students were smoking cigarette and 31.4 % were using alcohol. It was determined that 74.5 % of the students knew what the drug substance was and 57.8 % knew the hazards of drug substances.Conclusion: Substance dependency comprises one of the most important health problems. In the research it was observed that the substance usage rates among high school students were significantly lower than that of reported in other countries.
Keywords: Smoking; alcohol; adolescent; substance abuse